Histological description of the reproductive system of male and female hatchlings of the Magdalena river turtle (Podocnemis lewyana) (2014)
ABSTRACT: In this study we described the macroscopic and microscopic histology of the reproductive system of male and female Podocnemis lewyana neonates (3.5 months old). We found macroscopic differences in the morphology of the gonads between the sexes, with ovaries being twice as long as testes, and testes being twice as wide as ovaries. Microscopically, we identified several immature elements, such as the lack of a muscle layer in the oviduct of females, and simple epithelia instead of pseudostratified epithelia in the oviduct and epididymis described in reptile adults. We also found a black pigment observed macroscopically in the mesovarium, and macroscopically and histologically in the epididymis. This pigment is consistent with the center of melano-macrophages described in other vertebrates. Finally we described a supporting mesenchymal structure, the appendage of the oviduct, which was much longer than what has been described in other Podocnemis species.